Peramalan Pertumbuhan Bank Syariah Indonesia Pasca Kebijakan Merger - Yenny Kornitasari; Ide Wahyu Safitri; Ilham Wanakusuma; Dita Indah Safitri (ITB AAS INDONESIA Surakarta, 2022)
This research aims to forecast the growth of PT Bank Syariah Indonesia Tbk. after the merger policy which is reviewed through three variables, namely assets, financing, and third party funds. The method used in doing the forecast is Double Exponential Smoothing and Linear Trend Line Model. The forecast result using Double Exponential Smoothing shows that the assets of Bank Syariah Indonesia will continue to grow to 327 trillion rupiah in December 2023. The financing and third party funds also shows significant growth. In December 2023, financing of Bank Syariah Indonesia shows a figure of up to 60 trillion rupiah and third party funds will increase by 282 trillion rupiah. Meanwhile, forecasting using the Linear Trend Line Model also shows growth of up to 295 trillion rupiah in asset variables. The financing variable shows a forecast of an increase of 74 trillion rupiah and the third party fund variable which is predicted to grow to 256 trillion rupiah in December 2023. Assets that continue to grow indicate that there is an increase in the performance of Bank Syariah Indonesia. On the financing side, it shows a projected stable growth throughout 2023. This shows that the economic recovery period due to the pandemic does not affect the financing side of Bank Syariah Indonesia. Meanwhile, growth in third party funds indicates that the public is increasingly loyal and familiar with Bank Syariah Indonesia.